Edible Bird’s Nest (EBN) sample preparation for research studies / Ainin Nadhirah Abd Manan ... [et al.] - Abd Manan, Ainin Nadhirah; Sunarharum, Wenny Bekti; Abdul Muttalib, Siti Azima; Hajar, Nadya; Tan, Eddie Ti Tjh (2021)
Edible Bird’s Nests (EBN) research works have seen a growing trend. Most of the EBN related studies involved solubilisation and solid-liquid separation before further analysis. However, there was a lack of examination on the solubilisation and separation techniques for EBN. Hence, this paper reported the examination of the EBN solubilisation methods and comparison of the solid-liquid separation techniques that were carried out previously. The collected data were based on the electronic literature search of Web of Science (WOS) and ScienceDirect. The literature search in the databases indicated the majority of the EBN processing related studies show the use of enzymatic solubilisation. It is a preferred solubilisation method and likely more effective than the use of non-enzymatic solubilisation. It is interesting to find that the data presentation for EBN solubility between enzymatic and non-enzymatic solubilisation was distinct. The solubility studies of enzymatic solubilisation were usually reported in the form of degree of hydrolysis (DH) while the non-enzymatic solubilisation reported the protein solubility. Besides that, it was found that the use of filter paper (Whatman No.1 and No.4) was the most frequently used solid-liquid separation method in EBN studies. In conclusion, enzyme solubilisation and filter paper filtration have emerged as preferable solubilisation and solid-liquid separation methods for EBN related research.